The Implementation of Classical Guidance through Canva-Based Project-Based Learning to Improve Senior High School Students’ Learning - Tio Yoga Pratama; Muslikah Muslikah; Herie Gunawan (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: This study was driven by the low level of students’ learning discipline, as reflected in behaviours such as tardiness, lack of classroom orderliness, and delays in submitting assignments. These conditions highlight the need for innovative classical guidance services that align with current technological developments to foster more structured and responsible learning habits. Objective: The study aimed to enhance the learning discipline of tenth-grade students at SMA Negeri 12 Semarang through the implementation of classical guidance using a Canva-based Project-Based Learning (PjBL) model. Method: This research employed a Classroom Action Research (CAR) design conducted in a pre-cycle, Cycle I, and Cycle II. Each cycle consisted of planning, action, observation, and reflection stages. The participants were 33 tenth-grade students. Data were collected using questionnaires and observation sheets to assess students’ learning discipline in each cycle. Results: The findings showed a gradual improvement in students’ learning discipline across cycles. This improvement was reflected in the increasing percentage of students categorised as disciplined and highly disciplined, as well as in enhanced responsibility, punctuality, and active participation in learning activities. Conclusion: The implementation of classical guidance through a Canva-based PjBL model proved effective in improving students’ learning discipline. Contribution: Practically, this study provides an alternative technology-based classical guidance service model. Theoretically, it strengthens the application of Classroom Action Research in developing students’ disciplinary character within a digital learning environment.